1993
DOI: 10.3171/jns.1993.78.1.0026
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for complex partial seizures: surgical technique, safety, and efficacy

Abstract: Electrical stimulation of the vagus nerve has shown efficacy in controlling seizures in experimental models, and early clinical trials have suggested possible benefit in humans. Eleven patients with complex partial seizures were subjected to implantation of vagus nerve stimulators. Electrode contacts embedded in silicone rubber spirals were placed on the left vagus nerve in the low cervical area. A transcutaneously programmable stimulator module was placed in an infraclavicular subcutaneous pocket and connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 22 publications
0
61
0
3
Order By: Relevance
“…In fact, one trial noted a 6% median increase in seizure frequency with low VNS. 8 There were also significant differences in the percentage of patients considered responders (Ն50% reduction in seizure frequency), consisting of 22 to 39% of patients in the high VNS group versus only 13 to 19% of those in the low VNS group. The use of the hand-held magnet by patients and caregivers to activate the NCP generator directly in response to auras or simple-partial seizures has also reduced the severity of evolving seizures.…”
Section: Clinical Outcome Of Vns In Adults With Refractory Epilepsymentioning
confidence: 97%
See 3 more Smart Citations
“…In fact, one trial noted a 6% median increase in seizure frequency with low VNS. 8 There were also significant differences in the percentage of patients considered responders (Ն50% reduction in seizure frequency), consisting of 22 to 39% of patients in the high VNS group versus only 13 to 19% of those in the low VNS group. The use of the hand-held magnet by patients and caregivers to activate the NCP generator directly in response to auras or simple-partial seizures has also reduced the severity of evolving seizures.…”
Section: Clinical Outcome Of Vns In Adults With Refractory Epilepsymentioning
confidence: 97%
“…8,21,50,51 These trials demonstrated a mean or median seizure frequency reduction of 24 to 31% over 3 months of follow-up in patients receiving the high VNS treatment paradigm (i.e., VNS at therapeutic stimulatory parameters, such as 30 Hz, 30 s on, 5 min off, and 500-ks pulse width). This improvement was significantly greater than that found in patients in the low or subtherapeutic VNS group (e.g., 1 Hz, 30 s on, 90 -180 min off, 1.30-ks pulse width); these patients experienced a mean or median seizure frequency reduction of only 6 to 15%.…”
Section: Clinical Outcome Of Vns In Adults With Refractory Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Esto es importante porque los parámetros eléctricos constituyen una variable fundamental relacionada con el control de las crisis y otros aspectos fisiológicos 40 .…”
Section: Figura 5 Instantánea Quirúrgica Del Electrodo Tunelizado Y unclassified